AKTIVITAS ANTIMIKROBA EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana) TERHADAP BAKTERI Aeromonas hydrophila, Edwardsiella tarda DAN JAMUR Saprolegnia sp. - Madiah Handayani; Dwi Suryanto; Tajuddin Siregar; Zulhan Efendi (AQUACOASTMARINE, 2015)
This study was aimed to know antimicrobial potential of extract of mangosteen rind(Garcinia mangostana) against bacteria Aeromonas hydrophila, Edwardsiella tarda andfungus Saprolegnia sp. and to know the extract toxicity to brine shrimp (Artemia salinaLeach.). Mangosteen rind was extracted using methanol, ethyl acetate and n-hexane.Antimicrobial activity test was done using the agar diffusion method. To know thecompounds contained in the extract phytochemical test was conducted. The chemicalcompound test showed that extract of mangosteen rind contains phenolic/tannin/flavonoid,terpen/steroid dan alkaloid. The extracts inhibitated the growth of Aeromonas hydrophila,Edwardsiella tarda and Saprolegnia sp. to some extent. The optimal antimicrobial activitywas obtained from ethyl acetate. The extract showed cytotoxic activity with LC50<1000μg/ml.Keywords : Antimicrobial activity, Aeromonas hydrophila, Edwardsiella tarda, Garciniamangostana, Saprolegnia sp.